Mineralogy, Classification, and Tectonic Setting of the Granitic Pegmatites of New York State, USA - M. V. Lupulescu; J. R. Chiarenzelli; Bailey, D. G. (The Canadian Mineralogist, 2012)
Pegmatites in New York State are largely restricted to areas of exposed Precambrian basement rocks, including the Adirondack Mountains and the Hudson Highlands. In the Adirondacks, they were emplaced into rocks that were metamorphosed during the Grenville orogeny to either the upper amphibolite facies (Adirondack Lowlands) or the granulite facies (Adirondack Highlands). Their mineral assemblages range from simple to complex, with localized occurrences of: (a) Be-, Al-, and B-rich species such as beryl, chrysoberyl, sillimanite, dumortierite, and tourmaline-supergroup minerals, (b) rare-element- and rare-earth-element-bearing minerals such as columbite-(Fe), uranopolycrase, fergusonite-(Y), uraninite, xenotime-(Y), and monazite-(Ce), (c) Ca-, F-, and K-dominant amphiboles, (d) phosphates (fluorapatite, isokite, wagnerite), (e) sulfides (bismuthinite, molybdenite), and (f) tungstates (scheelite). The pegmatite bodies from southern New York State and from some of the southern Adirondack locations display mineralogical zoning, typically with a quartz-rich core. Post-emplacement metamorphic features are observed in pegmatites in the northwestern Adirondack Lowlands, but are negligible or obscured in most of those from the southern and eastern Adirondacks. On the basis of the metamorphic grade of the host rocks, all New York pegmatites belong to the Abyssal class, whereas on the basis of mineralogy and inferred tectonic setting, they show affiliations to the NYF and mixed NYF–LCT pegmatite families. Pegmatites in the Adirondack Lowlands are related to the calc-alkaline arc magmatism of the Antwerp–Rossie granite suite and yield U–Pb zircon crystallization ages that indicate intrusion during the late Shawinigan orogeny (~1195 Ma); currently there are no known pegmatites related to the Ottawan and Rigolet orogenies in the Lowlands. Pegmatites in the Highlands yield U–Pb zircon crystallization ages that correspond to: (a) emplacement during the late Elzevirian (~1222 Ma), and metamorphism during the late Shawinigan (~1178 Ma) orogenies; (b) emplacement during the early (1098 Ma) and mid to late Ottawan orogeny (~1062–1025 Ma); (c) intrusion during the early Rigolet orogeny (1009–1003 Ma), and finally, (d) intrusion related to a thermal pulse at 949 Ma, possibly associated with the Cathead Mountain leucocratic dike swarm (935 ± 9.2 Ma). Few, if any, granitic pegmatites were intruded between 1178 and 1098 Ma in the Adirondack Highlands. The main pegmatite bodies in the Adirondack Highlands occur in association with extensional A-type granites such as the Hawkeye and Lyon Mountain Granite suites. These rocks were emplaced in response to orogenic collapse following the Ottawan orogeny. At present, relatively little can be concluded about the tectonic setting of pegmatites in southern New York.
Keywords: geology